Legal regulation for a labor inspector: A comparative study between Iraqi legislation and the Algerian and Bahraini legislation - رشيد, صبا نعمان; جياد, ضاري مطرود (Journal of Legal Sciences, 2021)
The labor inspector may be exposed - while performing his duties that are legally assigned to him - to threats or attacks on him by employers, which makes it impossible for the inspector to perform these jobs.This has prompted international and Arab labor inspection standards, as well as national labor laws, to emphasize the need to provide security support and legal protection for the labor inspector, and to punish employers' violators, with the aim of extending the authority and prestige of the state and ensuring the enforcement of laws and thus achieving the goals for which it was legislated.